Oral Presentations Abstracts: HOW SMART ARE SMART MATERIALS? A CONCEPTUAL AND ETHICAL ANALYSIS - DE KANTER, Anne-Floor J.; JONGSMA, Karin R.; BREDENOORD, Annelien L. (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Today, a person can receive a hip implant to replace a deformed, swollen hip joint or a pacemaker to sustain the beating rhythm of their heart. Thanks to Regenerative Medicine, soon, it may become possible not just to replace, but to re-grow healthy tissues after injury or disease. To this end, tissue engineers are designing ‘smart’, ‘life-like’ biomaterial implants to activate the inherent regenerative capacity of the human body. Such a smart life-like biomaterial may for example stimulate re-growth of a fresh, living heart valve after implantation in a patient’s heart. However, the meaning of the smartness and lifelikeness of these synthetic biomaterials is conceptually unclear. Therefore, in this paper, we first aim to unravel the meaning of the terms ‘smart’ and ‘life-like’, and next, analyse what ethical and societal implications are associated with this new generation of biomaterial implants as a result. Our conceptual analysis reveals that the biomaterials are considered ‘smart’ because they can communicate with human tissues and ‘life-like’ because they are structurally similar to these tissues. Moreover, the biomaterial artifacts are designed to integrate to a high degree with the living tissue of the human body. While these characteristics provide the biomaterials with their therapeutic potential, we argue that it complicates a) the irreversibility of the implantation process, b) questions of ownership regarding the biomaterial implant, and c) the sense of embodiment of the receiver of the implant. Overall, timely anticipation and consideration of these ethical challenges will promote responsible development of biomaterials in Regenerative Medicine.